2001
DOI: 10.2337/diabetes.50.10.2384
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Markers of Inflammation to the Development of Glucose Disorders in the Elderly

Abstract: Several studies suggest that inflammation plays a role in the pathogenesis of some glucose disorders in adults. We tested this hypothesis in a longitudinal cohort study of older individuals who had normal fasting glucose (FG) values at baseline. We compared the baseline levels of six inflammatory markers in participants who had developed glucose disorders at follow-up with those of participants whose FG remained normal at follow-up. Participants were members of the Cardiovascular Health Study, a prospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
316
5
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 514 publications
(362 citation statements)
references
References 42 publications
28
316
5
8
Order By: Relevance
“…For example, TNF-α decreases insulin secretion from pancreatic cells [35] and insulin signalling in pancreatic cells, white adipose tissue, liver and muscle [35,36]. Plasma IL-6 [7], CRP [7,37,38] and orosomucoid [6] were predictors of the incidence of type 2 diabetes in several large prospective studies (ranging from 1,047 to 27,000 subjects and with up to 7-year follow-up), independently of other correlates of plasma glucose and insulin sensitivity [6,7,37,38]. Thus, as these inflammatory markers are elevated in hyperapoB women, we hypothesise that hyperapoB women may be at a greater risk of developing, not only CHD, but type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TNF-α decreases insulin secretion from pancreatic cells [35] and insulin signalling in pancreatic cells, white adipose tissue, liver and muscle [35,36]. Plasma IL-6 [7], CRP [7,37,38] and orosomucoid [6] were predictors of the incidence of type 2 diabetes in several large prospective studies (ranging from 1,047 to 27,000 subjects and with up to 7-year follow-up), independently of other correlates of plasma glucose and insulin sensitivity [6,7,37,38]. Thus, as these inflammatory markers are elevated in hyperapoB women, we hypothesise that hyperapoB women may be at a greater risk of developing, not only CHD, but type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…There is heterogeneity between studies, with some demonstrating an independently positive association of CRP with incident diabetes [3][4][5][6][7][8][9][10][11], while others show no association after adjustment for adiposity and insulin resistance [12][13][14][15]. Differences in the association between CRP and diabetes by sex have also been reported [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies have demonstrated that elevated circulating concentrations of several acute-phase proteins, cytokines, chemokines and soluble adhesion molecules precede the development of type 2 diabetes by many years [8][9][10][11][12][13][14]. Among these immune mediators, C-reactive protein (CRP) and IL-6 have been investigated for potential associations with incident type 2 diabetes in most prospective studies.…”
Section: Introductionmentioning
confidence: 99%